2016
DOI: 10.1038/srep33017
|View full text |Cite
|
Sign up to set email alerts
|

Identification and testing of oviposition attractant chemical compounds for Musca domestica

Abstract: Oviposition attractants for the house fly Musca domestica have been investigated using electrophysiological tests, behavioural assays and field tests. Volatiles were collected via head space absorption method from fermented wheat bran, fresh wheat bran, rearing substrate residue and house fly maggots. A Y-tube olfactometer assay showed that the odor of fermented wheat bran was a significant attractant for female house flies. Bioactive compounds from fermented wheat bran for house fly females were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
(53 reference statements)
1
9
0
1
Order By: Relevance
“…Pig manure was reported to attract more flies than others manures. This is probably due to the fermentation odor which is a significant attractant for female house flies (Tang et al, 2016). This observation made by the farmers corroborates the observation of Bouafou (2011) who showed that pig manure is among the most suitable substrates for fly larvae production.…”
Section: Identification Of Organic Substrate Attracting Fly Larvaesupporting
confidence: 86%
See 1 more Smart Citation
“…Pig manure was reported to attract more flies than others manures. This is probably due to the fermentation odor which is a significant attractant for female house flies (Tang et al, 2016). This observation made by the farmers corroborates the observation of Bouafou (2011) who showed that pig manure is among the most suitable substrates for fly larvae production.…”
Section: Identification Of Organic Substrate Attracting Fly Larvaesupporting
confidence: 86%
“…Soil fertility is currently at the center of the debates on sustainability of production systems in Sub-Saharan Africa. The fertility of the productive soils of this region is declining (Hodomihou et al, 2011;Saïdou et al, 2012;Sossa-Vihotogbé et al, 2013). This phenomenon is accelerated by inadequate practices such as exclusive use of inorganic fertilizers, burning and export of crop residues without proper restitution measures (Saïdou et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…EAG recordings were used to identify electrophysiological activities of H. halys at each developmental stage (female and male adults, and nymphal larvae). Each antenna of the brown marmorated stink bug was prepared following the standard procedures of cutting its tip and base and immediately mounting the excised antenna between two glass capillary Ag/AgCl electrodes filled with Kaissling saline (Tang et al, 2016 ). The electrode at the distal end of the antenna was connected through an interface box to a signal acquisition interface board (IDAD; Syntech, Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…GC-EAD system was used to screen for bioactive chemical compounds following standard protocols as described previously [64]. Antennae were processed by cutting both extremes and immediately mounted with two glass capillary Ag/AgCl electrodes containing Kaissling saline [64] and an identical gas chromatography column was used under the same temperature program as for chemical analysis with the detector at 230 o C. The electrode at the distal end of the antenna was connected via an interface box to a signal acquisition interface board (IDAC; Syntech, Kirchzarten, Germany) connected to a computer. Electroantennogram signals and flame ionization detector responses from the gas chromatography were recorded simultaneously.…”
Section: Methodsmentioning
confidence: 99%